Protective role of Broccoli powder against continuous ingestion of Escitalopram antidepressant drug induced hepatotoxicity in Swiss albino male mice - Sneha Saxena; Lata Shahani; Pradeep Bhatnagar (International Journal of Phytomedicine, 2017)
To investigate the protective role of broccoli powder “Brassica Oleracea Italica” against continuous ingestion of escitalopram antidepressant drug induced hepatotoxicity in Swiss albino male mice. Mice were divided into different groups. Group1: Normal control (0.9% NaCl), Group 2: Escitalopram drug treated only (20 mg/kg), Group 3: Broccoli powder with Escitalopram drug treated (200 mg/kg + 20 mg/kg), Group 4: Olive oil vehicle control, Group 5: Carbon tetrachloride (CCl4) referenced as positive control (33 mg/kg), Group 6: Broccoli powder with CCl4 treated (200 mg/kg + 33 mg/kg). The effect of these groups on liver tissue was studied after three different time periods for 4, 8 and 12 weeks. The results showed that the treatment with escitalopram drug displayed significantly increased serum SGOT, SGPT, ALP level and alter liver antioxidant enzymes level (LPO, SOD and GSH) that are comparable with CCl4intoxicated group considered as positive control. Comparing escitalopram drug treated group with group that received both broccoli powder and escitalopram drug displayed a significant decrease in serum SGOT, SGPT, ALP levels and restored the level of antioxidant enzymes. The protective effect of broccoli powder on escitalopram drug induced hepatotoxicity was also supported by histopathological studies.